Study the association of body mass index and obesity in MBBS students with their family health status in a Tertiary Care Hospital, Puducherry - Suresh Pichandi; Vasu, Ganesh; Janakiraman Pichandi; Muraliswaran Perumal (Asian Journal of Medical Sciences, 2022)
Background: Overweight-obesity has turned into a worldwide epidemic due to sedentary lifestyle with more eating and less physical activity. The overweight and obesity rising among young people give alarm which may cause the formation link to the rise of other non-communicable diseases such as hypertension, diabetes, myocardial infarction, and stroke are the most important concern. Medical students are exposing lot of stress in their education and this stressful condition leads to irregularity in diet, lack of exercise, and their family health history, each being considered an independent factor leading to obesity. Aims and Objectives: The aim of the study was to estimate the prevalence of overweight and obesity among 2nd year MBBS students and find the association between family history with body mass index (BMI). Materials and Methods: This study included 150 MBBS students’ BMI survey from SVMCHRC, Puducherry The height and weight of the students were be measured and BMI was calculated using formula. Students parents health status data were collected and the association of BMI and family history was established. Results: Based on student BMI details, the study found that overweigh was 18% and obese was 38%. Student parents health details obtained and studied possible future risk for obese student. Conclusion: Students are overweight-obese that particular students family history was collected. They are susceptible to the future development of cardiovascular disease, Type II diabetes, hypertension, osteoarthritis, anesthesia risks, and menstrual abnormalities as well as some types of cancers including those of colon and breast. So that students necessary health promotional activities are suggested to adopt healthy life style including regular physical exercises, yoga, and good dietary habits that are advised for healthy life style.